Strategi Ketahanan Bisnis pada Usaha Kecil dan Menengah (UKM) Menghadapi Bencana - Rahmat, Hayatul Khairul (Journal of Current Research in Management, Policy, and Social Studies, 2025)
This paper explores strategies for enhancing business resilience in small and medium enterprises (SMEs) in disaster-prone areas. SMEs are essential for the local economy but face significant challenges in maintaining operations during and after a disaster. This study identifies key strategies for building resilience in SMEs, including risk management, business continuity planning, and the adoption of digital technologies. Using a literature review methodology, the research highlights the role of governmental and private sector support in enhancing SMEs' resilience. Case studies from various disaster-prone regions are examined to demonstrate the effectiveness of these strategies. The paper concludes by providing actionable recommendations for SMEs to develop robust resilience strategies and contribute to the long-term economic stability of their communities.